The Efficacy of Using Communicative Language Teaching (CLT) in Teaching Writing Descriptive Text to Indonesian English as Foreign Language (EFL) Students - Yanpitherszon Liunokas (Institut Agama Islam Negeri Palopo, 2021)
This research aims at finding out the efficacy of using Communicative Language Teaching (CLT) in teaching writing especially descriptive text to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of CLT effective in teaching conditional sentences to Indonesian EFL students?. The research can be an addition to the persisting teaching writing in English particularly the descriptive text through the use of CLT. The research was conducted in August 2019. This research was conducted at First semester students of the English Study Program of Nusa Cendana University, Kupang. The population of this research was First semester students of the English Study Program of Nusa Cendana University, Kupang in the 2020/2021 academic year. The number population is 160 in four classes.. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering writing descriptive text and the post-test given to find out the students’ improvement in mastering writing descriptive text after giving the treatment by using CLT. The findings show that using CLT is effective in teaching writing descriptive text to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use the CLT in developing students’ writing descriptive of Indonesian EFL students.